Determinants of ethical work behaviour of Malaysian public sector auditors - Ismail, Suhaiza; Yuhanis, Nursia (Emerald Publishing Limited, 2018)
Purpose – The study aims to investigate factors affecting ethical work behaviour among Malaysian public sector auditors. Based on Hunt and Vitell model, there are four research objectives for this study: (1) to investigate the influence of ethical climate on public sector auditors ethical work behaviour; (2) to examine the effect of professional commitment on ethical work behaviour of public sector auditors; (3) to investigate the effect of corporate ethical values on ethical work behaviour of public sector auditors; and (4) to examine the effect of ethical ideology on ethical work behaviour of public sector auditors.